PENGARUH BUDAYA ORGANISASI, PENGENDALIAN INTERNAL, PROACTIVE FRAUD AUDIT DAN WHISTLEBLOWING SYSTEM TERHADAP PENCEGAHAN FRAUD DALAM PENGELOLAAN DANA BOS - Devi Melinda; Enung Nurhayati; Dendi Purnama (Program Studi Akuntansi, Universitas Kuningan, 2023)
This study aims to examine the effect of organizational culture, internal control, proactive fraud audit, and whistleblowing system on fraud prevention in BOS fund management. This research was conducted using descriptive and verification methods. The population is all vocational high schools in Kuningan Regency as many as 45 vocational high schools. The sampling technique in this study was carried out with the type of probability sampling, namely simple random sampling. The sample used in this study were 31 vocational high schools in Kuningan Regency with 124 respondents Data collection techniques using a questionnaire with data analysis tools in the form of multiple linear regression analysis. The results of this study indicate that organizational culture, internal control, proactive fraud audit and whistleblowing system have a simultaneous and significant effect on fraud prevention in BOS fund management, organizational culture has a significant positive effect on fraud prevention in BOS fund management, internal control has a significant positive effect on prevention fraud in BOS fund management, proactive fraud audit has a significant positive effect on preventing fraud in BOS fund management, and the whistleblowing system has a significant positive effect on fraud prevention in BOS fund management Keywords: Organizational Culture, Internal Control, Proactive Fraud Audit, Whistleblowing System and Fraud Prevention in BOS Fund Management.